2018
DOI: 10.1111/jpc.14189
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of protocols for clinical trials in children submitted to ethics committees

Abstract: Protocols of trials involving children assessed by ethics committees generally include details on background and basic design, but many key domains in trial design and conduct are not covered. Despite widespread recognition of how problems in the design and conduct of trials may lead to unreliable results, investigators still appear to be omitting key elements in trial protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…The sample of the original study within each of the included meta-research studies varied. One meta-research study surveyed congress delegates [ 29 ], one study examined first-submission protocols for randomized controlled trials submitted to four hospital ethics committees [ 17 ], and 14 studies examined randomized or quasi-randomized primary studies published during a specific time period in a range of journals [ 10 , 11 , 18 , 21 28 , 31 , 32 , 34 ] or in specific databases [ 16 , 19 , 20 , 30 ]. Finally, one study examined the use of previously published systematic reviews when publishing a new systematic review [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sample of the original study within each of the included meta-research studies varied. One meta-research study surveyed congress delegates [ 29 ], one study examined first-submission protocols for randomized controlled trials submitted to four hospital ethics committees [ 17 ], and 14 studies examined randomized or quasi-randomized primary studies published during a specific time period in a range of journals [ 10 , 11 , 18 , 21 28 , 31 , 32 , 34 ] or in specific databases [ 16 , 19 , 20 , 30 ]. Finally, one study examined the use of previously published systematic reviews when publishing a new systematic review [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…A confused ethical analysis continues to frustrate efforts to reduce this threat. [44][45][46] We have attempted to show why the responsibilities of RECs extend beyond judging individual research proposals. The British ethicist Richard Ashcroft has made the welcome suggestion that RECs might take into account and use their influence to promote and protect the interests of non-participants in research and future patients.…”
Section: Improving the Relevance And Efficiency Of Research Ethics Reviewmentioning
confidence: 99%
“…The CONSORT statement and other reporting guidelines, promoted by groups such as the Enhancing the QUAlity and Transparency Of health Research (EQUATOR) network, have sought to improve the completeness of trial reporting. However, deficiencies in reporting are still found in areas such as study protocols, 37 consent and recruitment, 38 description of the primary outcome 39 and reports to data monitoring committees 40 . Reporting guidelines are used inappropriately and authors have even been found to ‘spin’ the wording of articles to distort the interpretation of results 41,42 .…”
Section: Reporting and Publicationmentioning
confidence: 99%